METODE DAKWAH DALAM MEMBENTUK AKHLAK MAHMUDAH REMAJA - Nurseri Hasnah Nasution (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
Virtue is a psychological phenomenon that permeates the soul, actions arising from it easily, without using it first consideration. If that appears good deeds and praise by reason and Personality 'is called with good morals (mahmudah). Conversely, if the bad deeds arise so-called bad manners (mazmumah). Moral graph mazmumah among adolescents in recent years is increasing. Propagation method requires an effective and efficient. Among the methods of moral propaganda in shaping teenagers into mahmudah is the method of lecture, question and answer, discussion, uswah (example), the conditioning.